Multijunction Si photocathodes with tunable photovoltages from 2.0 V to 2.8 V for light induced water splitting. Issue 1 (12th October 2015) - Urbain, Félix; Smirnov, Vladimir; Becker, Jan-Philipp; Lambertz, Andreas; Yang, Florent; Ziegler, Jürgen; Kaiser, Bernhard; Jaegermann, Wolfram; Rau, Uwe; Finger, Friedhelm
Abstract : Bias-free solar water splitting is demonstrated using thin film silicon based triple and quadruple junction solar cells with solar-to-hydrogen efficiencies up to 9.5%. Abstract : We report on the development of high performance triple and quadruple junction solar cells made of amorphous (a-Si:H) and microcrystalline silicon (μc-Si:H) for the application as photocathodes in integrated photovoltaic–electrosynthetic devices for solar water splitting. We show that the electronic properties of the individual sub cells can be adjusted such that the photovoltages of multijunction devices cover a wide range of photovoltages from 2.0 V up to 2.8 V with photovoltaic efficiencies of 13.6% for triple and 13.2% for quadruple cells. The ability to provide self-contained solar water splitting is demonstrated in a PV-biased electrosynthetic (PV-EC) cell. With the developed triple junction photocathode in the a-Si:H/a-Si:H/μc-Si:H configuration we achieved an operation photocurrent density of 7.7 mA cm −2 at 0 V applied bias using a Ag/Pt layer stack as photocathode/electrolyte contact and ruthenium oxide as counter electrode. Assuming a faradaic efficiency of 100%, this corresponds to a solar-to-hydrogen efficiency of 9.5%. The quadruple junction device provides enough excess voltage to substitute precious metal catalyst, such as Pt by more earth-abundant materials, such as Ni without impairing the solar-to-hydrogen efficiency.